IMPEDANCE ANALYSIS FOR FOUR TYPES OF MINERAL WATER AND AQUADES USING ELECTRICAL IMPEDANCE SPECTROSCOPY (EIS) AT FREQUENCIES OF 1 Hz - 50 kHz - Wulandari, Darmawati; Zarkasi, Ahmad; Nurhanafi, Kholis (Indonesian Physical Review, 2024)
The Electrical Impedance Spectroscopy (EIS) method can be used to identify minerals in mineral water. The EIS method measures the impedance of a material by injecting alternating current in a certain frequency range, which is non-invasive and non-destructive. This study aims to analyze the impedance of mineral water and aquades based on the influence of the dissolved content using EIS equipment that provides flexibility in adjusting the desired frequency spectrum. The study used a frequency range from 1 Hz to 50 kHz with a four-electrode configuration. The measurement graph results were analyzed using Bode graph with impedance plot and phase shift angle to determine the impedance characteristics of mineral water. Equivalent circuit modeling helped to identify the electrochemical properties of materials such as the Warburg circuit, Constant Phase Element (CPE), and Randles circuit. The results show that the aquades has a higher impedance compared to the four mineral waters. Additionally, the four mineral waters exhibit varying impedances, attributed to their respective mineral content. Mineral water is characterized by an impedance that is dominated by Warburg impedance (Zw) at low frequencies, charge transfer resistance (Rct) and double layer capacitance (Cdl) at middle frequencies, and electrolyte resistance at high frequencies. However, the impedance of aquades dominated by electrolyte resistance (Re) at low frequency and Re+Rct at high frequency.